PENGARUH CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL MODERATING - Suhartanti, Tutut; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to examine the influence of corporate governance mechanism which is proxy by managerial ownership, institutional ownership, and the number of commissioners which is moderated by financial performance to the firm value. The population has been obtained by using purposive sampling method on the companies which are listed in Indonesian Stock Exchange (IDX) during the 2010-2013 periods and it is based on the determined criteria then nine automotive companies have been selected as samples. The examination of the hypothesis has been done by using multiple linear regression analysis and the SPSS application. it can be concluded indicate from the analysis that the financial performance has an impact on corporate governance mechanism and simultaneously it has positive and significant impact on the firm value. it means that the enhancement of company performance and the implementation of corporate governance mechanism. Thus, the trust of the investors will rise and it will be responded positively through the enhancement of the stock price of the company which can increase the firm value.Keywords: Managerial Ownership, Institutional Ownership, the number of the Board of Commissioner, Financial Performance, Firm Value